Rapid load transition for integrated solid oxide fuel cell – Gas turbine (SOFC-GT) energy systems: A demonstration of the potential for grid response. (15th April 2022) - Zhang, Biao; Maloney, Daniel; Farida Harun, Nor; Zhou, Nana; Pezzini, Paolo; Medam, Anudeep; Hovsapian, Rob; Bayham, Samuel; Tucker, David
Highlights: Demonstration of a rapid load change strategy (∼50% in 10 s) for SOFC-GT hybrids. Cyber-physical system integrating hardware with high-fidelity models was tested. The SOFC was protected without violating operational constraints during load change. Non-linear response points to the needs in developing adaptive automatic controls. Hardware-based co-simulation enables faster transition to zero-carbon power systems. Abstract: Rapid load transition is an essential requirement for integrated energy systems to maintain grid resilience as more renewable resources are added to the grid. Integrated solid oxide fuel cell – gas turbine (SOFC-GT) systems can provide high efficiency and low carbon emissions over a broad range of turndown. These hybrids also have the potential to enable rapid grid response. The challenge has been to demonstrate effective control strategies to manage load transitions. In the present study, a load transition of ∼50% was achieved in 10 s using a novel but simple strategy. Power demand on the SOFC and the GT were ramped down concurrently. During this transition, the SOFC anode fuel was manipulated to maintain SOFC fuel utilization while the cathode inlet air flow and temperature were also manipulated to thermally protect the SOFC. This study was conducted using the Hybrid Performance (Hyper) facility at the National Energy Technology Laboratory (NETL) in a co-simulation environment with the Idaho National Laboratory (INL)'s grid-simulation. The load ramping strategy was tested using a hardware-based cyber-physical simulation methodology. The results demonstrate a high-fidelity representation of SOFC-GT hybrid dynamics and validation of the control strategy. Thermal and electrochemical transients indicated that the SOFC was well protected during rapid load turndown without violating operability constraints. This demonstration revealed the non-linear nature of tightly coupled SOFC-GT system components, especially the non-linear response of SOFC cathode air flow and inlet temperature controls. These results highlight the needs and challenges in developing adaptive automatic controls for autonomous rapid load transitions. This work demonstrates that SOFC-GT hybrids are a viable option to provide the fast-ramping characteristics essential to accommodate high levels of variable renewable power while maintaining grid resilience, reliability, and environmental performance. The results also demonstrate the utility of co-simulation in advancing the tightly-coupled integrated energy systems needed to meet goals for zero-carbon power generation.